Implementasi Model Pembinaan SMK Pengimbasan Oleh SMK Pusat Keunggulan dalam Meningkatkan Kualitas Pembelajaran Berbasis Teaching Factory - Samuel Dody Setiawan; Valiant Lukad Perdana Sutrisno (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
This study aims to describe the Teaching Factory coaching model implemented by Center of Excellence Vocational Schools in improving the quality of learning in impact vocational schools and to identify the factors influencing the success of the coaching process. This study employed a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews, observations, and documentation involving principals, Teaching Factory coordinators, productive teachers, students, and industrial partners selected using purposive and snowball sampling techniques. Data validity was tested through source and method triangulation, while data were analyzed using an interactive analysis model consisting of data collection, reduction, display, and conclusion drawing. The results showed that the Teaching Factory coaching model was implemented through interconnected stages, including coaching forms and strategies, implementation, monitoring and evaluation, and program impact. The coaching process was conducted through socialization, workshops, training, direct practice, and continuous mentoring using learning by doing and model imitation approaches. The implementation of Teaching Factory improved industry-oriented learning systems and strengthened teacher and student competencies in production-based learning. The success of the coaching process was influenced by internal factors, such as school commitment, teacher support, student readiness, human resources, and facilities, as well as external factors, including industrial support, government support, funding, public trust, and industrial collaboration.